Giving or receiving feedback: which is more beneficial to students' learning?. Issue 1 (2nd January 2019) - Ion, Georgeta; Sánchez Martí, Angelina; Agud Morell, Ingrid
Abstract: Assessment is a key component of the education process and strategies involving peer-feedback are considered beneficial to student learning. This study aims to analyse the benefits giving and receiving feedback have for students' development of cognitive and metacognitive, affective and professional competences. One-hundred and eighty-eight students enrolled in teacher education answered a survey. Results indicate that, after providing feedback, the students perceived a better learning experience and an increased sense of commitment to their own learning and their colleagues' progress. A key finding from this study was the role of students in their own learning. As most participants recognised, providing feedback helped them improve their learning, which is a clear indicator that students want to adopt an active role in their own learning and consider their involvement critical in the design of teaching and learning experiences. To achieve the greatest advantages, feedback must be accompanied by tutoring and mentoring to ensure positive connections with the task, address doubts and clarify the comments received.